2011
DOI: 10.1002/mds.23800
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of complications related to deep brain stimulation hardware

Abstract: Deep brain stimulation is a therapeutic technique increasingly used in the treatment of a variety of neurological, psychiatric, and pain disorders. Although beneficial, it carries the immediate and long-term risks associated with implanted hardware in the brain parenchyma and subcutaneous tissue. The most common hardware complications include electrode migrations or misplacements, wire fractures, skin erosion, infections, and device malfunction. We systematically reviewed the literature on deep brain stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 73 publications
1
35
2
Order By: Relevance
“…This may also explain why in our study the proportion of lead fractures was significantly higher in patients with VIM DBS (usually indicated for ET) compared to STN DBS. These results, however, should be interpreted with caution as these differences have not been reported in previous studies and the multivariate analysis did not show any difference in complication rate with respect to the underlying disorder; therefore an independent effect of the underlying diagnosis to the different hardware complications was not confirmed in our study [10]. We were not able to demonstrate dystonia as a risk factor for hardware complications or lead fractures, as suggested by other authors [18].…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…This may also explain why in our study the proportion of lead fractures was significantly higher in patients with VIM DBS (usually indicated for ET) compared to STN DBS. These results, however, should be interpreted with caution as these differences have not been reported in previous studies and the multivariate analysis did not show any difference in complication rate with respect to the underlying disorder; therefore an independent effect of the underlying diagnosis to the different hardware complications was not confirmed in our study [10]. We were not able to demonstrate dystonia as a risk factor for hardware complications or lead fractures, as suggested by other authors [18].…”
Section: Discussioncontrasting
confidence: 53%
“…Fractures may occur at different levels, but they tend to occur usually where the electrode enters the connection cable [10,11,12,13,26]. In our study, only 1 patient had a history of severe trauma preceding lead damage; to our knowledge no study has demonstrated that trauma is significantly associated with lead fractures [26,27].…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations